Post-disasters solid waste management : case studies and thematic analysis - Kaja, Ranim (2015)
This thesis presents four case studies as examples of how different countries around the world deal with their disaster waste management. These case studies are the Great East Japan Earthquake, Hurricane Katrina, Sri Lanka earthquake and tsunami, and finally man-made conflicts. Disaster solid waste management is not old in the management planning. In the past, the countries facing disasters used to struggle, and they focused more on removing the debris from streets and sensitive places like main roads and hospitals. However, they did not really have any plan about how to deal with the generated waste and debris, where the stressful situation of the emergency phase right after the disaster made the case even more complicated. Disasters can generate extremely massive amount of debris and waste depending on its nature and the affected area’s nature. Additionally, there will be also the daily generated waste, which means that disasters will significantly affect all life aspects, especially the economy. Therefore it is important to have a well prepared disaster waste management plan to limit the potential damage and to minimize the cost and the time needed for the recovery phase. Moreover, the waste and debris in the affected area will cause a significant environmental impact. Therefore, the responsible authorities have to manage the disaster waste sustainably and work on bringing the area to an environmentally accepted situation. By presenting different methods of disaster solid waste management in four different countries, it will be possible to spot the best practices and the wrong practices in the management system. The removal of debris is the most important factor at the emergency phase in the waste management, as it will help reaching the victims and prevents the spread of diseases. However, the authority should be prepared with the place of where to take the debris and waste, and what to do with them in the next stages. In this thesis more detailed information about the disaster solid waste management practices will be explained to clarify the fundamental differences in facing different types of catastrophes in countries with different levels of development.